2017
DOI: 10.1002/slct.201701906
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Spirocyclopropane‐Linked Pyrazolones from Azomethine Ylides via C(sp3)‐H Activation

Abstract: A novel synthesis of spirocyclopropane‐1,4′‐pyrazolin‐5′‐one derivatives via iodine‐mediated C(sp3)–H activation is described. Thus, a diastereoselective synthesis of spirocyclopropane‐linked pyrazolones from 4‐arylidene‐3‐methyl‐1‐phenylpyrazolin‐5‐ones and azomethine ylides, generated in situ from iodine‐catalyzed reaction of 2‐methylquinoline or acetophenones with pyridine in the presence of base, has been developed. These transformations proceeded via a cyclopropanation reaction followed by anti‐eliminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Representative synthetic strategies toward these spiro skeletons include intramolecular cyclization, [4a,b,g] [2+1] annulation reaction, [4e,k] cascade reaction [4h,j,l–n] . In this context, annulation reactions of arylidenepyrazolones with chlorides, [3f,5] ammonium ylides [4i,6] and arsonium ylide [7] provided classical approaches (Scheme 1). Although impressive results have been achieved in synthesis of spirocyclopropanyl pyrazolone derivatives, it is still highly desirable to develop general and efficient process to benefit the synthesis of this spiro skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Representative synthetic strategies toward these spiro skeletons include intramolecular cyclization, [4a,b,g] [2+1] annulation reaction, [4e,k] cascade reaction [4h,j,l–n] . In this context, annulation reactions of arylidenepyrazolones with chlorides, [3f,5] ammonium ylides [4i,6] and arsonium ylide [7] provided classical approaches (Scheme 1). Although impressive results have been achieved in synthesis of spirocyclopropanyl pyrazolone derivatives, it is still highly desirable to develop general and efficient process to benefit the synthesis of this spiro skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our studies on the synthesis of spirans, herein, we report an efficient synthesis of a novel series of functionalized spiroindolo[2,1‐ b ]quinazolines via 1,4‐dipolar cycloaddition reaction between the Huisgen intermediates and tryptanthrin‐malononitrile adducts in CH 2 Cl 2 under catalyst‐free conditions at room temperature (25°C), in 75% to 91% yields. The pyridopyridine or pyridoquinoline skeletons are fascinating structural motifs, which attracted the attention of synthetic chemists in recent years …”
Section: Introductionmentioning
confidence: 99%
“…(Figure ). Over the past few years, spirocyclic pyrazole compounds have received considerable interest due to their unique structural features and extensive reaction possibilities. , Several synthetic methods for constructing spiropyrazolones have been developed, including the Diels–Alder reaction, 1,3-dipolar cycloaddition reaction, spirocyclopropanation, etc. Recently, in 2021, Su et al reported the synthesis of spirocyclic pyrazole consisting of a cyclopropane ring system using sulfide catalysis …”
mentioning
confidence: 99%
“…Based on the existing literature and our previous research, , we hypothesized that arylidene/alkylidine-pyrazolones might serve as interesting C2/C4 synthons. These compounds could undergo Michael addition with the C1 synthon ammonium ylide followed by intramolecular substitution, resulting in the formation of spirocyclic or bicyclic privileged scaffolds (Figure ).…”
mentioning
confidence: 99%